Restaurant ordering system using mobile application - Nur Hanis, Ihsan (2011)
The Restaurant Ordering System Using Mobile Application is designed for servers to be used in any restaurant The server of this system is represented by waiters of the restaurant itself.By using this system,the servers will take orders from the customers using wireless technology typically with a mobile device.The order that is taken by mobile is communicates to the main server through local wireless intranet.The main server is the server at the counter that control all the system such as bill calculation,order reception,and also order delivery from the servers to the restaurant departments.The restaurants have two different departments that is cashier department and kitchen department.At the kitchen department,the order will display at the kitchen's screen.This system has two main categories, which are the administrator and user(waiter).The administrator uses very simple power full easy to use the system interface where as the user uses wireless interface for taking orders from the customers.